Advances in Poultry Nutrition Research 2021
DOI: 10.5772/intechopen.96013
|View full text |Cite
|
Sign up to set email alerts
|

Essential Nanominerals and Other Nanomaterials in Poultry Nutrition and Production

Abstract: Poultry production, health and wellbeing are highly dependent upon formulation of balanced rations in terms of energy, protein, and micronutrients (vitamins and minerals). Among all, minerals are required in fewer quantities, but they are very important to maintain the productivity in poultry. Minerals present in the feeds are less bioavailable and additional supplementation is obligatory to meet the physiological demands of poultry. Conventionally, minerals are supplemented as inorganic salts, which are less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Inorganic selenium (Se IV , Se VI ) requires two steps of reduction (oxidizing GSH) to be transformed to the active metabolite, while the organic form is metabolised by selenocysteine lyase via a process that does not include the oxidation step [67]. Elemental selenium in the nano size, on the other hand, has an unclear path of metabolism due to the much reduced particle size that does not resemble the bulk material and follows the mechanism of nanoparticles uptake and metabolism [85].…”
Section: Selenium and Selenoproteinsmentioning
confidence: 99%
“…Inorganic selenium (Se IV , Se VI ) requires two steps of reduction (oxidizing GSH) to be transformed to the active metabolite, while the organic form is metabolised by selenocysteine lyase via a process that does not include the oxidation step [67]. Elemental selenium in the nano size, on the other hand, has an unclear path of metabolism due to the much reduced particle size that does not resemble the bulk material and follows the mechanism of nanoparticles uptake and metabolism [85].…”
Section: Selenium and Selenoproteinsmentioning
confidence: 99%
“…In cattle breeding, the application of nanoformulated selenium and zinc enhanced animal resistance and improved milk production capacity [ 204 ]. The addition of Zn-based NPs to the diet led to an increase in performance, rumen fermentation, and antioxidant system activity in calves [ 205 ] and goats [ 206 ]. Selenium NPs increased selenoprotein (Sel) gene expression and the selenium concentration in the milk of lactating dairy cows [ 207 ] and improved the feed assimilation and rumen fermentation in sheep [ 208 ].…”
Section: Current Applications Of Nanomaterials In Veterinary Medicinementioning
confidence: 99%
“…In this manner, the utilisation of selenium nanoparticles in poultry nourishment is suggested due to its impacts on the quality and quantity of products and the reduction of environmental pollution, especially in conditions of various types of stress (Abdel‐Moneim et al., 2021 ; Patra & Lalhriatpuii, 2020 ). Due to the vital role of selenium in reproductive physiology and follicle production, adding it to the diet is a common strategy to improve health and egg production (Swain et al., 2021 ). Previous researchers' results have shown that adding 0.25–0.3 mg of selenium nanoparticles per kilogram of a diet of laying hens increases the production and content of selenium in eggs (El‐Ramady et al., 2014 ; Yu et al., 2022 ).…”
Section: Previous Research In Layersmentioning
confidence: 99%